STUDI MORFOMETRIK, MERISTIK, DAN POLA PERTUMBUHAN IKAN BELIDA (Notopterus notopterus Pallas, 1769) DI SUNGAI SAIL KOTA PEKANBARU PROVINSI RIAU - Elly Anggriani Purba; Deni Efizon; Ridwan Manda Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Featherback fish (Notopterus notopterus) is a type of freshwater fish that inhabit theSail River. This fish has high economic value, the price is more than Rp 60.000/kg.Information on biological aspects of this fish, including morphometric, meristic, andgrowth patterns is rare. To understand the those characteristics, a research had beenconducted from March-April 2017. There were 100 fishes (116-299 mm TL and 8.6-234gr BW) captured from the river. There were 23 morphological characteristics measuredand 8 meristical characteristics counted. The meristical characteristics were as follows:D.6-7, P.11-14, V.1, A.99-111, the number of scale in the pre-dorsal fin was 102-103,around the body was 126-136, in the caudal peduncle was 12-14, and in the lateral linewas 150-168. The length-weight relationship shown that the growth of male and femalewas positive allometric (b= 3.363). The water quality parameters shown thattemperature 28-30°C, transparency 5.50-14.83 cm, pH 5-6, DO 2-3.8 mg/L, CO2 11.9-21.9 mg/L and depth 0.7-1.8 m. Data on water quality in the Sail River is able tosupport the life of the N. notopterus.Keywords: Notopterus notopterus, Sail River, morphometric, meristic, growth patterns